Effectiveness of Fobio Biopesticide Concentration and Soil Sterilization Interval for Controlling Stem Rot Disease by Fusarium oxysporum in Vanilla planifolia - Nurul Laily; Sri Wiyatiningsih; Arika Purnawati (Universitas Labuhanbatu, 2025)
Background: Stem rot disease caused by Fusarium oxysporum is one of the major diseases affecting vanilla plants (Vanilla planifolia A.), which can cause losses of up to 100%. Current management practices rely heavily on synthetic pesticides and often lack precision, raising environmental concerns and need for sustainable disease management strategies. This study aimed to determine the effectiveness of Fobio biopesticide concentration and soil sterilization intervals as control methods in suppressing the development of vanilla stem rot disease. Methodology: The study was conducted in vivo in Wonosalam Village, Jombang Regency using a factorial completely randomized design (CRD) with factors of Fobio biopesticide concentration (5 mL/L, 10 mL/L, and 15 mL/L) and application interval (1-week and 2-week intervals). The data were analyzed statistically using the Analysis of Covariance (ANCOVA). The parameters observed included disease intensity, infection rate, and biopesticide effectiveness. Findings: The results showed that the initial disease intensity had a very significant effect on the final intensity. The treatment with an application interval of once a week reduced disease intensity to 23.89%, lower than the interval of 2-weeks (26.67%) and the control (46.66%). A concentration of 15 ml/L reduced disease intensity to 24.94%, with the highest effectiveness also obtained in the 15 ml/L treatment at 1-week intervals (50.29%). The interaction between interval and concentration was also not significant, indicating that the effect of concentration did not change depending on treatment interval. The biopesticide Fobio was found to be sufficiently effective in suppressing the development of vanilla stem rot, and applications with more frequent intervals showed the highest efficacy. Contribution: This study highlights the importance of integrating biopesticide concentration and application interval while adjusting for initial disease intensity in vanilla stem rot management.